Changes in Bcl-2 and Bax Expression in Rat Tongue during 4-Nitroquinoline 1-oxide-induced Carcinogenesis - Nishimura, A. (Journal of dental research, 1999)
Bax is considered as a main effector of apoptosis. Bax forms homodimers and also heterodimers with Bcl-2. The function of the Bax-Bax dimer in active cell death is antagonized by Bax-Bcl-2 heterodimers. Thus, the ratio of Bcl-2 and Bax should control the susceptibility of cells to those stimuli that induce apoptotic cell death. An increase in apoptotic change has been shown in many carcinomas. In the present study, the changes in Bcl-2 and Bax expression in the tissue during carcinogenic transformation were examined immunohistochemically by means of the 4-nitroquinoline 1-oxide (4NQO)-induced carcinoma model. Animals were divided into 7 groups of 10 rats each, and given 50 ppm 4NQO solution as drinking water for 4, 8, 12, 16, 20, or 24 weeks. Ten animals were used as controls. Gradual increases in the numbers of Bcl-2- and Bax-positive cells were shown corresponding to the progression of experimental carcinogenesis. Statistically significant differences in Bcl-2 and Bax expression were demonstrated between control and four-week treatment groups (p < 0.01), and between control and eight-week treatment groups (p < 0.05), respectively. Levels of both proteins remained high after the period of dysplastic change of the epithelium. In conclusion, Bcl-2 and Bax are involved in the progression of 4NQO-induced carcinoma.